Mrs. Doubtfire [videorecording (DVD)] - Columbus, Chris; Williams, Robin, 1951-2014; Williams, Robin, 1951-2014; Field, Sally; Brosnan, Pierce; Fine, Anne (Twentieth Century Fox Home Entertainment, 2015)
A divorced man disguised as a woman takes a job as his ex-wife's housekeeper to be near his children.